Adolescent talus body fracture with high displacement: A case report. Issue 35 (August 2018) - Hama, Shunpei; Onishi, Ryu; Yasuda, Masataka; Minato, Kenta; Miyashita, Masahiro
Abstract: Rationale: Talus fracture is relatively rare in adults. Furthermore, talus fracture in pediatric population is rarer than in adult population. Although undisplaced talus fractures can be treated conservatively, most of talus fractures with displacement require surgical treatment in both pediatric and adult patients. In addition, avascular necrosis and arthrosis are the main complications of displaced talus fracture. Patient concerns: A 14-year-old boy was referred to our hospital owing to foot injury sustained on jumping off about 10 stairs. Diagnosis: Highly displaced talus body fracture of the dome and the posterior process. Interventions: Because the Linhart classification of this case was III-C and instability at the fracture site persisted even after closed reduction, we performed arthroscopic-assisted reduction and internal fixation (ARIF) using headless screws and an external fixator under general anesthesia. Outcomes: We removed the external fixator at 3 months after the surgery. At the 1-year follow-up, the patient was able to walk with full weight bearing and his Japanese Orthopaedic Association score recovered from 9 points before the surgery to 95 points. The range of motion of dorsiflexion and plantarflexion was 10° and 60°, respectively, which were similar to that on the left side. No signs of bone necrosis or arthrosis were observed on imaging. Lessons: ARIF with external fixation might be the treatment of choice for such a case.